The Effectiveness of Jump To Box Exercises on Increasing the Power of Leg Muscles in Volleyball Players - Tang, Aco; Cholifah, Ifanny Nur; Thahir, Muh; Lestari, Virny Dwiya (UNIVERSITAS NEGERI MAKASSAR, 2024)
Muscle power is the ability of muscles to perform their strongest contractions at maximum speed. This study aims to determine the effect of Jump Box training on increasing muscle explosiveness in volleyball players of SMAN 21 Makassar. This type of research is a quasi-experimental with a nonequivalent pre-test – post-test control group design approach, which was carried out at SMAN 21 Makassar with a population of 28 people who met the inclusion criteria divided into 2 groups with a total sampling technique, namely the experimental group given Jump To Box exercises and the control group without jump to box exercises. This study uses the Vertical Jump Test to measure the increase in muscle explosiveness. The data obtained from the Shapiro-Wilk normality test with a result of p> 0.05, the influence test used was a paired sample t-test with results in both groups, namely p = 0.000 (p <0.05) which means that both experimental and control groups have an effect and can provide significant results on muscle explosive power. Then based on the independent sample t-test, the p-value = 0.005 (p <0.05). Because the p-value = 0.005 <0.05 means that there is a significant difference between the experimental group with Jump To Box training and the control group without Jump To Box training on increasing muscle explosive power. The conclusion of this study is Jump To Box exercise is effective on increasing muscle explosiveness in volleyball players.